USM-TORAY REACHES UNDERSTANDING TO STRENGTHEN COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 21 September 2016 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman today held discussions with the Managing Director of Toray Industries (Malaysia) Sdn. Bhd., Masahiko Kawamura and Group HR, Legal & Compliance Head, Toray Group (Malaysia) of Companies, Gor Siew Yeng.